Community engagement, social context and coverage of mass anti-malarial administration: Comparative findings from multi-site research in the Greater Mekong sub-Region - Pell, Christopher L. (PLoS One, 2019)
BACKGROUND: Between 2013 and 2017, targeted malaria elimination (TME), a package of interventions that includes mass drug administration (MDA)–was piloted in communities with reservoirs of asymptomatic P. falciparum across the Greater Mekong sub-Region (GMS). Coverage in target communities is a key determinant of the effectiveness of MDA. Drawing on mixed methods research conducted alongside TME pilot studies, this article examines the impact of the community engagement, local social context and study design on MDA coverage. METHODS AND FINDINGS: Qualitative and quantitative data were collected using questionnaire-based surveys, semi-structured and in-depth interviews, focus group discussions, informal conversations, and observations of study activities. Over 1500 respondents were interviewed in Myanmar, Vietnam, Cambodia and Laos. Interview topics included attitudes to malaria and experiences of MDA. Overall coverage of mass anti-malarial administration was high, particularly participation in at least a single round (85%). Familiarity with and concern about malaria prompted participation in MDA; as did awareness of MDA and familiarity with the aim of eliminating malaria. Fear of adverse events and blood draws discouraged people. Hence, community engagement activities sought to address these concerns but their impact was mediated by the trust relationships that study staff could engender in communities. In contexts of weak healthcare infrastructure and (cash) poverty, communities valued the study’s ancillary care and the financial compensation. However, coverage did not necessarily decrease in the absence of cash compensation. Community dynamics, affected by politics, village conformity, and household decision-making also affected coverage. CONCLUSIONS: The experimental nature of TME presented particular challenges to achieving high coverage. Nonetheless, the findings reflect those from studies of MDA under implementation conditions and offer useful guidance for potential regional roll-out of MDA: it is key to understand target communities and provide appropriate information in tailored ways, using community engagement that engenders trust.